Ultrasonic Assisted Synthesis of 2, 3-Dihydroquinazolin-4(1H)-ones Involving Three-Component Reaction of Isatoic Anhydride, Amines and Pyrazole Carbaldehydes Catalyzed by [γ-Fe2O3@HAp-SO3H] - Sina, Kiana F.; Yahyazadeh, Asieh; Mahmoodi, Nosrat O.; Moghadam, Kurosh R.; Nikpassand, Mohammad; Rasa, Mahdi (Letters in Organic Chemistry, 2020)
The combination of [γ-Fe2O3@HAp-SO3H] as a catalyst and ultrasonic effect catalyzed the synthesis of diverse derivatives of 2, 3-dihydroquinazolin-4(1H)-ones which is reported in this study. The products were synthesized via the one-pot three-component reaction of isatoic anhydride, amines and pyrazole carbaldehydes in water: EtOH catalyzed by recoverable [γ-Fe2O3@HAp-SO3H]. This paper conducted an investigation of the effect of various solvents, temperatures and catalysts on the reactions. Short reaction times, mild reaction conditions, simple work-up, the desired yields and the use of an appropriate catalyst are the advantages of this novel method. The new derivatives were validated by using FT-IR, 1HNMR, and 13CNMR. Moreover, the synthesized compounds were screened for their antimicrobial activity against bacterial strains.
Keywords: [γ-Fe2O3@HAp-SO3H]